2012
DOI: 10.1051/0004-6361/201219794
|View full text |Cite
|
Sign up to set email alerts
|

Dust-trapping Rossby vortices in protoplanetary disks

Abstract: Context. One of the most challenging steps in planet formation theory is the one leading to the formation of planetesimals of kilometre size. A promising scenario involves the existence of vortices able to concentrate a large amount of dust and grains in their centres. Up to now this scenario has mostly been studied in 2D razor thin disks. A 3D study including, simultaneously, the formation and resulting dust concentration of the vortices with vertical settling, is still missing. Aims. The Rossby wave instabil… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(112 citation statements)
references
References 52 publications
3
109
0
Order By: Relevance
“…Meheut et al (2012b) show that large dust particles can greatly affect their parent vortices. Thus, a more complete work is needed to answer the question of whether a vortex can maintain its shape while growing a planet.…”
Section: Discussionmentioning
confidence: 99%
“…Meheut et al (2012b) show that large dust particles can greatly affect their parent vortices. Thus, a more complete work is needed to answer the question of whether a vortex can maintain its shape while growing a planet.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of a large-scale vortex can be triggered in protoplanetary disks due to baroclinic instability (Klahr & Bodenheimer 2003;Lyra & Klahr 2011;Raettig et al 2013;Lyra 2014) or the Rossby wave instability (RWI) via the coagulation of smaller-scale vortices (Lovelace et al 1999;Li et al 2000Li et al , 2001Lyra et al 2009b;Meheut et al 2010Meheut et al , 2012aMeheut et al , 2012bMeheut et al , 2012cMeheut et al , 2013Richard et al 2013;Flock et al 2015). Barge & Sommeria (1995) and Klahr & Henning (1997) have already shown that particles tend to get trapped in anticyclonic vortices.…”
Section: Introductionmentioning
confidence: 99%
“…These papers have addressed the formation of the vortices, their stability and their interaction with dust particles. We refer for example to Meheut et al [5] for a recent study and for up-to-date references.…”
Section: Resultsmentioning
confidence: 99%